Developing a Creative Curriculum to Cultivate Elementary School Students’ Interest in Learning - Yamamoto, Sota; Tanaka, kaito; Suzuki, Ren (Yayasan Adra Karima Hubbi, 2024)
The interest in learning among elementary school students is a critical factor in shaping their academic success and lifelong learning attitudes. However, traditional teaching methods often fail to engage students, leading to a decline in their enthusiasm for learning. This study aims to develop a creative curriculum designed to cultivate elementary school students’ interest in learning by incorporating interactive and student-centered learning activities. The research employs a mixed-methods approach, combining qualitative data from classroom observations and interviews with teachers and students, along with quantitative data from pre- and post-intervention surveys measuring student engagement and interest in learning. The findings suggest that the implementation of a creative curriculum significantly increased students’ interest in learning across various subjects, with noticeable improvements in student participation, curiosity, and motivation. Teachers also reported higher levels of engagement and enthusiasm during lessons. This study concludes that a creative curriculum can effectively enhance students’ interest in learning by fostering a more dynamic, interactive, and personalized learning environment. The implications of this research highlight the importance of adopting innovative teaching strategies to ensure that students develop a lasting interest in their education.